Skunk River virus, a novel orbivirus isolated from Aedes trivittatus in the United States. (11th January 2019) - Tangudu, Chandra S.; Charles, Jermilia; Hurt, Stefanie L.; Dunphy, Brendan M.; Smith, Ryan C.; Bartholomay, Lyric C.; Blitvich, Bradley J.
Abstract : The genomic organization and in vitro host range of a novel mosquito-associated orbivirus, designated Skunk River virus, is described. The virus was isolated from Aedes trivittatus collected in Iowa in the United States. Three recognized viruses were also recovered: Culex flavivirus (family Flaviviridae ), Houston virus (family Mesoniviridae ) and Umatilla virus (family Reoviridae ). The genome of Skunk River virus contains 10 segments and its organization is characteristic of viruses in the genus Orbivirus (family Reoviridae ). The coding region of each segment was fully sequenced, revealing that the greatest nucleotide identity was to the corresponding regions of Big Cypress orbivirus and Sathuvachari virus, two recently described mosquito-associated orbiviruses. The phylogenetic inference is in agreement with these findings. In vitro host range experiments revealed that Aedes, Anopheles and Culex cell lines, and select lepidopteran and rodent cell lines, are permissive to Skunk River virus replication. In conclusion, we provide evidence of a novel mosquito-associated orbivirus in Iowa.